Propuesta del plan estratégico de mercadeo para las redes sociales de Facebook e Instagram en la empresa RALCEIV S.A - Angulo-Salazar, Natalia (Instituto Tecnológico de Costa Rica., 2021)
The present Final Graduation Project will develop a strategic marketing plan on the social networks of Instagram and Facebook applied to the company RALCEIV S.A. The project will be divided into several chapters in which different important points will be developed and in which it will facilitate the project to be developed in the most orderly and appropriate way. In first instance, all the information of the company will be collected to have a better knowledge of its activities and its trajectory in the market, in addition to that, the general aspects that will be carried out throughout the project, as well as its scope, will be discussed, limitations, objectives, among others. In the second chapter all the information relevant to the project will be developed, such as the product itself, as business terms, as terms of the one that will be developed in the project. On this chapter, a lot of supporting information will be taken from books and internet pages according to the information that is required to better illustrate what the company's products consist of and what the methods that were going to be carried out in the project consist of. In the other hand, there will be a chapter to define the exact way in which the project was going to be carried out. It´s important that in all projects the behavior that this is going to have is defined and likewise define towards which sector it is focused. Therefore, the population in which the project is going to be addressed, the variables that the project will be facing and the strategies that will be carried out for the collection of pertinent data with the study will be considered. This next chapter is about the analysis of the data collected will be carried out in which the internal situation of the company is analyzed with information provided only about the company and the external situation of the company in which reliable internet pages will be consulted and the collection of data by means of surveys to know the opinion of the public. On the same way, the Strategic Marketing Plan will be presented, which will be developed in several stages: first, the current situation in which the company is located will be analyzed, in which it will also try to understand if the products offered by the company, they manage to satisfy the needs of the market that the company wants to address, among other things. It will also try to establish the marketing strategy that best suits the needs of the company. In the other hand, the budget that is needed to carry out this strategy will be analyzed. And finally, a marketing program will be created for the continuous and correct management of social networks.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2021.
Keywords: Ralceiv Sociedad Anónima; Costa Rica; Estrategia comercial; Mercadeo; Commercial strategy; Marketing